PERSEPSI MAHASISWA PROGRAM STUDI MAGISTER MANAJEMEN PENDIDIKAN ISLAM TERHADAP PEMBELAJARAN ONLINE - Baharuddin Baharuddin; Erwin Hafid; Danial Rahman; Lisa Nursita (Idaarah: Jurnal Manajemen Pendidikan, 2022)
This research is a quantitative descriptive study conducted at the Major of Islamic Education Management at Postgraduate of UIN Alauddin Makassar. Respondents in this study were determined using the saturated sample technique with the consideration that students who were still active in the study program made it possible to obtain data in a short time. Data collection techniques using questionnaires and structured interviews. The data obtained is then processed by organizing data based on student perceptions regarding the online lecture process, lecturer capabilities, and lecture facilities during online learning. Data were analyzed using quantitative descriptive analysis. The results of this study regarding the perceptions of students of the Islamic Education Management Masters Study Program at the Postgraduate Program of UIN Alauddin Makassar show that: (1) students feel that online learning is quite effective and efficient with an average proportion of responses of 70%; (2) lecturers during the Covid-19 pandemic had good capabilities with an average proportion of responses of 83.2%; and (3) the lecture facilities used are adequate with an average response proportion of 77.7% through the use of Zoom and Google Meet. It is hoped that this research will have implications for lecturers and students, especially in the Islamic Education Management Study Program at UIN Alauddin Makassar that online learning is a lecturing activity carried out during the Covid-19 pandemic which can still be carried out by utilizing various facilities and continuing to strive to improve capabilities for learning (for students) and teaching (for lecturers).